EKSPRESI WAJAH SEBAGAI SUMBER PENCIPTAAN KARYA SENI LUKIS - DEDI CHANDRA, Yasrul Sami, S.Sn., M.Sn, Drs. Suib Awrus, M.Pd (Serupa The Journal of Art Education, 2014)
The purpose of this thesis is revealing facial expressions in paintings in the style of post-IMPRESIONIST. The final work of the theme "Facial Expression as a Source of Creation Art Work", originated from the interest of authors see facial expressions gestures that appear every individual such as; feeling happy, sad, angry, moody, yelling and so forth. As it is applied in the creation of this work is through the assessment phase, the experimental phase, phase formation, and the finishing stage, to realize a 10 (ten) works of art in accordance with the desired theme.